Loan Loss Provisioning Practices in Hong Kong Banking Sector - chan, wing chong (2013)
In the wake of Global Financial Crisis 2008/2009, much attention has been placed on the pro-cyclicality of the banking system and the ability of the banks to absorb economic shocks; questions have been raised about the quality of the banks’ credit portfolios and the rigidness of the provisioning system. Whilst the current debate on the pro-cyclicality of the banking system has focused on the pro-cyclical effects of Basel II Capital Accord, little attention has been placed on the pro-cyclicality created by the provisioning system.